Effects of transformational leadership, work climate, and work engagement on teachers’ performance - Saipul Rahman; Aslamiah Aslamiah; Novitawati Novitawati (Universitas Pendidikan Indonesia, 2025)
This study is motivated by the crucial role of teachers in improving the quality of education in madrasahs, particularly in Madrasah Tsanawiyah Negeri (MTsN) in Barito Kuala Regency. The purpose of this research is to analyze the influence of transformational leadership of madrasah principals, work climate, and work engagement on teacher performance. This study employs a quantitative approach with an explanatory method, and data analysis was conducted using the SmartPLS program. The respondents consisted of 150 teachers from five MTsNs selected using a total sampling technique. The instrument used was a standardized questionnaire that had been tested for validity and reliability. The results indicate that transformational leadership has a positive and significant effect on teacher performance, work climate, and work engagement. Additionally, work climate and work engagement significantly influence teacher performance. The study also found an indirect effect of transformational leadership on teacher performance through the mediating roles of work climate and work engagement. These findings offer practical implications for strengthening madrasah leadership to improve teacher performance sustainably. Abstrak Penelitian ini dilatarbelakangi oleh pentingnya peran guru dalam meningkatkan kualitas pendidikan di madrasah, khususnya di Madrasah Tsanawiyah Negeri (MTsN) Kabupaten Barito Kuala. Tujuan penelitian ini untuk menganalisis pengaruh kepemimpinan transformasional kepala madrasah, iklim kerja, dan keterlibatan kerja terhadap kinerja guru. Penelitian ini menggunakan pendekatan kuantitatif dengan metode eksplanatori dan pengolahan data yang dilakukan melalui program SmartPLS. Responden berjumlah 150 guru dari lima MTsN yang dipilih melalui teknik total sampling. Instrumen yang digunakan berupa kuesioner terstandar yang telah diuji validitas dan reliabilitasnya. Hasil penelitian menunjukkan bahwa kepemimpinan transformasional berpengaruh positif dan signifikan terhadap kinerja guru, iklim kerja, dan keterlibatan kerja. Selain itu, iklim kerja dan keterlibatan kerja juga berpengaruh signifikan terhadap kinerja guru. Penelitian ini juga menemukan adanya pengaruh tidak langsung kepemimpinan transformasional terhadap kinerja guru melalui peran mediasi iklim kerja dan keterlibatan kerja. Temuan ini memberikan implikasi praktis dalam penguatan kepemimpinan kepala madrasah untuk meningkatkan kinerja guru secara berkelanjutan. Kata Kunci: iklim kerja; kepemimpinan transformasional kepala madrasah; keterlibatan kerja; kinerja guru